Developmental transitions involve common biological processes across living beings - Evan Force; Dominique Lamy; Stéphane Debernard; Arnould Savouré; Matthieu Dacher (Heliyon, 2025)
Pivotal biological processes unfold within a limited time during the life cycles of living beings. They are characterized by changes in morpho-anatomy, physiology, and/or in behavior, such as sexual maturation in many animals, flowering in plants, or sporulation in some unicellular organisms. Such events collectively represent transitions between distinct stages of the life cycle of organisms and are often termed “transitions of development” or “developmental transitions”. Although these terms are mentioned in biological literature, no definition has yet been established. We thus propose to define developmental transitions as adaptative events marked by modifications occurring at different biological scales ranging from biochemistry to ecology during a brief period in the life cycle of living beings, namely the passage from one developmental stage to another. From this definition, this review covers the similar mechanisms and functions of developmental transitions, drawing insights from extensively studied models as well as lesser-known examples, from unicellular to multicellular organisms of diverse taxonomic groups. Cross-checking works in various fields highlight that developmental transitions are underlain by common processes. Indeed, they require fundamental cellular mechanisms (e.g., proliferation, differentiation, apoptosis) that are tightly coordinated in time and space through molecular signaling pathways and genetic networks, which in turn are regulated by biotic and abiotic factors, thus reflecting adaptations to the environment. This broad and transverse perspective aims to highlight commonalities that transcend taxonomic boundaries, providing insights into the fundamental principles governing dynamic transformations of living organisms.